Associations of Voice Metrics with Postural Function in Parkinson’s Disease - Anna Carolyna Gianlorenço; Valton Costa; Walter Fabris-Moraes; Paulo Eduardo Portes Teixeira; Paola Gonzalez; Kevin Pacheco-Barrios; Ciro Ramos-Estebanez; Arianna Di Stadio; Mirret M. El-Hagrassy; Deniz Durok Camsari; Tim Wagner; Laura Dipietro; et al. (Life)
Background: This study aimed to explore the potential associations between voice metrics of patients with PD and their motor symptoms. Methods: Motor and vocal data including the Unified Parkinson’s Disease Rating Scale part III (UPDRS-III), Harmonic–Noise Ratio (HNR), jitter, shimmer, and smoothed cepstral peak prominence (CPPS) were analyzed through exploratory correlations followed by univariate linear regression analyses. We employed these four voice metrics as independent variables and the total and sub-scores of the UPDRS-III as dependent variables. Results: Thirteen subjects were included, 76% males and 24% females, with a mean age of 62.9 ± 10.1 years, and a median Hoehn and Yahr stage of 2.3 ± 0.7. The regression analysis showed that CPPS is associated with posture (UPDRS-III posture scores: β = −0.196; F = 10.0; p = 0.01; R2 = 0.50) and UPDRS-III postural stability scores (β = −0.130; F = 5.57; p = 0.04; R2 = 0.35). Additionally, the associations between CPPS and rapid alternating movement (β = −0.297; p = 0.07), rigidity (β= −0.36; p = 0.11), and body bradykinesia (β = −0.16; p = 0.13) showed a trend towards significance. Conclusion: These findings highlight the potential role of CPPS as a predictor of postural impairments secondary to PD, emphasizing the need for further investigation.